2013
DOI: 10.1073/pnas.1217358110
|View full text |Cite
|
Sign up to set email alerts
|

UBR box N-recognin-4 (UBR4), an N-recognin of the N-end rule pathway, and its role in yolk sac vascular development and autophagy

Abstract: The N-end rule pathway is a proteolytic system in which destabilizing N-terminal residues of short-lived proteins act as degradation determinants (N-degrons). Substrates carrying N-degrons are recognized by N-recognins that mediate ubiquitylation-dependent selective proteolysis through the proteasome. Our previous studies identified the mammalian N-recognin family consisting of UBR1/ E3α, UBR2, UBR4/p600, and UBR5, which recognize destabilizing N-terminal residues through the UBR box. In the current study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
83
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 78 publications
(90 citation statements)
references
References 21 publications
7
83
0
Order By: Relevance
“…Interestingly, we identify two new RAD6-associated E3 proteins, KCMF1 and UBR4, along with several additional interactors previously linked (via genetic and/or biochemical evidence) to intracellular vesicle trafficking and mitochondrial function. Using a combination of in vivo and in vitro binding assays combined with NMR spectroscopy, our data suggest that the KCMF1 protein recruits RAD6 to UBR4, a noncanonical N-recognin recently implicated in bulk lysosomal degradation and autophagy (11,12). Consistent with this observation, knockdown of KCMF1 or RAD6A expression alters late endosome-lysosome vesicle trafficking.…”
supporting
confidence: 69%
See 1 more Smart Citation
“…Interestingly, we identify two new RAD6-associated E3 proteins, KCMF1 and UBR4, along with several additional interactors previously linked (via genetic and/or biochemical evidence) to intracellular vesicle trafficking and mitochondrial function. Using a combination of in vivo and in vitro binding assays combined with NMR spectroscopy, our data suggest that the KCMF1 protein recruits RAD6 to UBR4, a noncanonical N-recognin recently implicated in bulk lysosomal degradation and autophagy (11,12). Consistent with this observation, knockdown of KCMF1 or RAD6A expression alters late endosome-lysosome vesicle trafficking.…”
supporting
confidence: 69%
“…UBR4 interacts with the Dengue virus protein NS5, and both KCMF1 and UBR4 interact with the Human Papilloma Virus (HPV) E7 proteins across a wide range of HPV isotypes (32)(33)(34). Notably, like the other N-recognins, UBR4 can bind to N-end rule substrates, and was recently linked to lysosomemediated degradation and autophagy (11,12). Consistent with these findings, UBR4 is also a candidate gene for episodic ataxia (EA), a group of rare human neurological channelopathies characterized by a lack of balance and coordination (35), and D. melanogaster strains mutant for the UBR4 ortholog pushover display sluggishness, a lack of coordina- (36).…”
Section: Rad6 Ap-ms Identifies a Set Of Novelmentioning
confidence: 99%
“…1B). The embryonic lethality of two different p600 null mouse strains (24,25), however, precluded an investigation of the mechanistic roles of p600 in adult brain neurons but hints at the requirement of p600 for cell survival in vivo. Because of this lethal phenotype and expression of p600 in the adult hippocampus (15) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Because we were unable to detect signs of the former two mechanisms, we are bound to suspect the latter. This suspicion is well grounded in the published role of p600 in the N-end rule pathway (50) and especially in new work (24) showing that p600 knock-out mice die during embryogenesis, with yolk sac development defects characterized by aberrant autophagy (elaborated in Ref. 51).…”
Section: Discussionmentioning
confidence: 99%
“…31 More recent studies have suggested that the Arg/N-end rule pathway is also implicated in autophagy and mitophagy. 32,33 A set of endoplasmic reticulum (ER)-residing chaperone proteins, including HSPA5/BiP/ GRP78 (heat shock protein family A [HSP70] member 5), P4HB/PDI (prolyl 4-hydroxylase subunit b), and DNAJC10/ ERdj5 (DnaJ heat shock protein family [Hsp40] member C10), were identified to be N-terminally arginylated, retrotranslocated to the cytosol, bound to misfolded proteins, and recognized by the autophagic receptor SQSTM1/p62 (sequestosome 1). 34 Although these proteins are likely to be cotargeted to the autophagosome, the biological functions of arginylated ER proteins, their catabolic regulation (for example, via UPS, autophagy, or both), and the implication of these proteins in autophagic flux remain essentially uncharacterized.…”
Section: Introductionmentioning
confidence: 99%